(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Against the problems of existing uterine contraction identification algorithms, mainly in the inapplicability to real-time identification of the characteristic points of uterine contraction wave, a novel method based on a series of criteria for real-time analysis is proposed in this paper. After confirming the beginning, end and peak of the analyzed segment, a series of criterion are used to identify the status of current uterine contraction point. Meanwhile, the status of current uterine contraction point is corrected by a buffer mechanism to ensure accuracy. The experiments show that the conformity between the realtime analysis results and two experts' analysis results are high, and the kappa coefficients are as high as 0.874 and 0.872. Moreover, the time required for the analysis of a uterine contraction point is only 0:003200060:0002 (mean 00b1 SD) seconds, which is far less than the acquisition and output time of a uterine contraction point by pressure probe. Therefore, the proposed method can meet the requirements of real-time analysis in both accuracy and efficiency.